Severe Hypoglycemia–Induced Fatal Cardiac Arrhythmias Are Augmented by Diabetes and Attenuated by Recurrent Hypoglycemia - Reno, Candace M. (Diabetes, 2017)
We previously demonstrated that insulin-mediated severe hypoglycemia induces lethal cardiac arrhythmias. However, whether chronic diabetes and insulin deficiency exacerbates, and whether recurrent antecedent hypoglycemia ameliorates, susceptibility to arrhythmias remains unknown. Thus, adult Sprague-Dawley rats were randomized into four groups: 1) nondiabetic (NONDIAB), 2) streptozotocin-induced insulin deficiency (STZ), 3) STZ with antecedent recurrent (3 days) hypoglycemia (∼40–45 mg/dL, 90 min) (STZ+RH), and 4) insulin-treated STZ (STZ+Ins). Following treatment protocols, all rats underwent hyperinsulinemic (0.2 units ⋅ kg(−1) ⋅ min(−1)), severe hypoglycemic (10–15 mg/dL) clamps for 3 h with continuous electrocardiographic recordings. During matched nadirs of severe hypoglycemia, rats in the STZ+RH group required a 1.7-fold higher glucose infusion rate than those in the STZ group, consistent with the blunted epinephrine response. Second-degree heart block was increased 12- and 6.8-fold in the STZ and STZ+Ins groups, respectively, compared with the NONDIAB group, yet this decreased 5.4-fold in the STZ+RH group compared with the STZ group. Incidence of third-degree heart block in the STZ+RH group was 5.6%, 7.8-fold less than the incidence in the STZ group (44%). Mortality due to severe hypoglycemia was 5% in the STZ+RH group, 6.2-fold less than that in the STZ group (31%). In summary, severe hypoglycemia–induced cardiac arrhythmias were increased by insulin deficiency and diabetes and reduced by antecedent recurrent hypoglycemia. In this model, recurrent moderate hypoglycemia reduced fatal severe hypoglycemia–induced cardiac arrhythmias.